2014
DOI: 10.3354/ame01716
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal expression of SAR11 proteorhodopsin and 16S rRNA genes in coastal North Atlantic waters

Abstract: Proteorhodopsins (PR) are phylogenetically widespread and highly expressed proton pumps in marine bacterial communities, including in the SAR11 clade, one of the most common clades in the oceans. The relationships between PR expression, light and cell activity remain unclear, especially in natural environments. We examined these relationships during 3 diurnal studies in spring, summer and fall in Delaware coastal waters. The abundance of genes and transcripts of SAR11 PR, SAR11 16S rRNA and total bacterial 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Rhodopsin-associated genes were also significantly reduced under these nutrient-deplete conditions, including carotenoid biosynthesis and β-carotene monooxygenase genes, which encode the final step in retinal synthesis (Table 1). These results show that rhodopsin is not simply constitutively transcribed in an OM43 clade representative and match recent metatranscriptomic and quantitative PCR studies that show modulation of rhodopsin transcription in situ , particularly on diel time scales (39, 40). While the physiological drivers of these modulations in the environment are not well understood, studies of several marine isolates have shown that organisms may use proteorhodopsin-derived energy to survive periods of starvation (41).…”
Section: Resultssupporting
confidence: 88%
“…Rhodopsin-associated genes were also significantly reduced under these nutrient-deplete conditions, including carotenoid biosynthesis and β-carotene monooxygenase genes, which encode the final step in retinal synthesis (Table 1). These results show that rhodopsin is not simply constitutively transcribed in an OM43 clade representative and match recent metatranscriptomic and quantitative PCR studies that show modulation of rhodopsin transcription in situ , particularly on diel time scales (39, 40). While the physiological drivers of these modulations in the environment are not well understood, studies of several marine isolates have shown that organisms may use proteorhodopsin-derived energy to survive periods of starvation (41).…”
Section: Resultssupporting
confidence: 88%
“…Similarly, in Delaware coastal waters an elevated abundance of PR genes belonging to SAR11 clade bacteria and Flavobacteriia was observed during daylight hours (112). A follow-up study in the same waters confirmed that SAR11 PR gene expression is higher (ϳ2.5-fold) during the day at different seasons (113). Using metatranscriptomic analysis on samples collected in southeast U.S. coastal waters, it was recorded that, in general, PR genes are abundantly expressed by a multitude of taxa (114).…”
Section: Environmental Rhodopsin Gene Expression Analysessupporting
confidence: 51%
“…Quantitative PCR assays in the coastal North Atlantic showed a tight correlation between SAR11 PR expression and photosynthetically active radiation, whereas growth-related gene activity did not (Lami and Kirchman, 2014), suggesting that energy collected from PR may be directed toward other functional responses, besides growth. Altogether, the presence of PR during the Polar darkness seems to involve several mechanisms and more functional complexity than reported from experiments.…”
Section: Seasonal Trends In Pr Presence and Expressionmentioning
confidence: 99%
“…Patterns in PR expression would be expected to vary seasonally and covary as a function of light availability; however, such patterns have rarely been explored. Recently, a study using a quantitative PCR approach on SAR11 populations from North Atlantic waters showed a strong correlation between PR expression and photosynthetically active radiation; however, no obvious growth response was observed (Lami and Kirchman, 2014). In the Arctic ocean, although PR genes have been reported during both lightreplete summer and light-limited winter at a coastal site , detailed longterm seasonal dynamics of PR's presence or expression in Polar oceans have yet to be described.…”
Section: Introductionmentioning
confidence: 99%